Homicides and socio-environmental determinants of health in Brazil: a systematic literature review - Clovis Wanzinack; Marcos Claudio Signorelli; Clóvis Reis (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2018)
Abstract: Brazil currently has the highest absolute number of homicides in the world, which results from a complex range of factors. This study aimed at understanding the associations between socio-environmental determinants of health (SDH) and homicides in Brazil through a systematic literature review. The review followed PRISMA guidelines, selecting quantitative and qualitative studies published in Portuguese, English, and Spanish carried out between 2002 and 2017, available in the PubMed, MEDLINE, LILACS, SciELO and BVS-BIREME databases. Two trilingual reviewers tracked studies independently by basing on the eligibility criteria. We critically assessed the selected studies with the Critical Appraisal Skills Programme (CASP) or the Checklist for Analytical Cross-Sectional Studies, depending on the study design. We considered 60 studies and grouped their SDH into categories to develop a narrative synthesis about each SDH. These categories were: territory; race/ethnicity; gender; age; social inequalities and economic factors; development; education; work and employment; drugs and trafficking; other SDH. We found some SDH were more associated with homicides, such as being young, black, male, of low education level, and also people who lived in places of high social inequality, such as urban suburbs and agricultural frontiers. Unemployment and drug trafficking, as well as intersections between various SDH were also prominent. Education seems to be a protective factor for homicide. Despite the limited capacity of interpretation due to the high range of methodological approaches, this review shows the importance of considering SDH and their intersections when developing homicide prevention policies.